Estimated some Antioxidant Enzymes and Trace Elements in some Iraqi Women Infected with Breast Cancer (Journal of the College of Basic Education, 2022)
Erythrocytes glutathione peroxidase (GPx) , catalase (CAT) and serum malondialdehyde (MDA), in addition to three trace elements including selenium, iron and zinc were determined in two groups of Iraqi women with breast cancer ( A and B) and compared with healthy control group ( group C) . Results have revealed that (GPx) activity was highly significance and significance increased in erythrocytes of groups A (37.2 ±6.5) U / gm Hb and B (30.5±5.1) U / gm Hb respectively compared with group C (28.5±4.5) U /gm Hb , while (CAT) activity was significant and highly significance increase in erythrocytes of groups A (2.55±0.45) U / gm Hb and B (2.16±0.25) U / gm Hb respectively compared with group C (1.65±0.25) U / gm Hb. Moreover , MDA level was highly significance increase in sera of groups A ( 12.2±4.3) mmol / L and B (18.6±5.6) mmol / L compared with group C (3.6±1.2) mmol / L. Results have also reported that selenium level was significantly increased in sera of groups A (65±9) ng/mL and B (59±10) ng/mL compared with group C ( 50±6) ng/mL. As well , iron level was non-significantly increased and significantly decreased in sera of group A (1.4±0.9) µg/ mL and B (0.9±0.1) µg /mL respectively compared with group C (1.2±0.5) µg/mL. Zinc level was significant and highly significance decreased in sera of groups A (0.77±0.21) µg/mL and B (0.98±0.14) µg/mL respectively compared with group C (0.66±0.22) µg / mL. . From the present study we concluded that MDA and Zn levels are good biochemical markers for breast cancer regardless the period of time for suffering from this disease and the duration of treatment, while GPx , CAT , Se and Fe could be considered biochemical markers only for the first two years of the disease.